The early landscape of coronavirus disease 2019 vaccine development in the UK and rest of the world. Issue 3 (8th July 2020) - Sharpe, Hannah R.; Gilbride, Ciaran; Allen, Elizabeth; Belij‐Rammerstorfer, Sandra; Bissett, Cameron; Ewer, Katie; Lambe, Teresa
Summary: Since the first World Health Organization notification on 31 December 2019, coronavirus disease 2019 (COVID‐19), the respiratory disease caused by the coronavirus severe acute respiratory syndrome coronavirus‐2 (SARS‐CoV‐2), has been responsible for over four million confirmed infections and almost 300 000 deaths worldwide. The pandemic has led to over half of the world's population living under lockdown conditions. To allow normal life to resume, public health interventions will be needed to prevent further waves of infections as lockdown measures are lifted. As one of the most effective countermeasures against infectious diseases, an efficacious vaccine is considered crucial to containing the COVID‐19 pandemic. Following the publication of the genome sequence of SARS‐CoV‐2, vaccine development has accelerated at an unprecedented pace across the world. Here we review the different platforms employed to develop vaccines, the standard timelines of development and how they can be condensed in a pandemic situation. We focus on vaccine development in the UK and vaccines that have entered clinical trials around the world. Abstract : The SARS‐CoV‐2 pandemic has accelerated vaccine development at an unprecedented pace across the world, whilst utilising novel platform technologies. This review summarises the main platforms employed for vaccine development, the standard timelines of development and how they can be condensed during a pandemic. We focus on vaccine candidate development in the UK, and vaccines which have progressed to phase I clinical trials in the UK and worldwide.